Integrasi Green Supply Chain Management dan Teknologi Digital dalam Meningkatkan Kinerja Berkelanjutan UMKM melalui Efisiensi Operasional sebagai Variabel Mediasi - Tetty Nur Intan Rifia; Fisy Amalia; Tohiroh Tohiroh (Jurnal Kewirausahaan Cerdas dan Digital, 2025)
Sustainability has become an important requirement for micro, small, and medium-sized enterprises (MSMEs) in the production and manufacturing sectors amid resource constraints, increasing waste generation, and rapid technological development. This study aims to examine the relationship between Green Supply Chain Management (GSCM), digital technology, and the sustainable performance of MSMEs, with operational efficiency serving as a mediating variable. A quantitative approach with an explanatory research design was employed, involving 100 MSME owners selected through purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that GSCM and digital technology contribute to improved operational efficiency, with coefficients of 0.421 and 0.386, respectively. GSCM and digital technology also contribute to sustainable performance, with coefficients of 0.218 and 0.241, while operational efficiency demonstrates the strongest contribution, with a coefficient of 0.447. Operational efficiency partially mediates the relationships between GSCM and digital technology and sustainable performance, with indirect effects of 0.188 and 0.173, respectively. These findings demonstrate that integrating green supply chain practices and digital technology, supported by operational efficiency, can strengthen the economic, social, and environmental performance of MSMEs and contribute to their long-term sustainability.